Analysis of the Satisfaction Level of Rental Simple Flat (Rusunawa) in the Management of the Surabaya City Government Reviewing on Building Quality - Pemal Kabogi; Fredy Kurniawan; Hendro Sutowijoyo (LPPM NAROTAMA UNIVERSITY, Indonesia, 2022)
The construction of Rusunawa is one of the ideas or solutions in providing livable housing for Low-Income Communities (MBR) to overcome the chaos of urban spatial planning. Based on data from the Surabaya City Land and Building Management Office as the manager of the Rusunawa owned/controlled by the Surabaya City Government, the average Rusunawa tenants in the City of Surabaya have lived in the Rusunawa for more than 3 years. This shows that most of the residents of the Rusunawa feel comfortable living in the Rusunawa. This study aims to determine the condition of Rusunawa Penjaringansari Phase IV, Rusunawa Siwalankerto Phase II, and Rusunawa Keputih Phase III in terms of building quality. Whereas in addition to the above, it also aims to determine the level of occupant satisfaction with the quality of the Rusunawa building so that a Rusunawa repair strategy is obtained using Importance Performance Analysis (IPA) analysis. That based on the results of the study, the occupants said that the condition of the Penjaringansari Flats Phase IV, Siwalankerto Flats Phase II, and Keputih Rusunawa Phase III according to the residents when viewed from the quality side of the building showed an average percentage of 80.51% which qualitatively had a very good rating. While the level of satisfaction of the residents of Rusunawa on the quality of the building shows an average percentage of 82.64% which qualitatively has a very satisfied assessment. Whereas the improvement strategy at Penjaringansari Flats Phase IV, Siwalankerto Flats Phase II, and Keputih Rusunawa Phase III uses Importance Performance Analysis (IPA), namely by making improvements to indicators or attributes contained in Quadrant A (Main Priority) such as providing vehicle parking facilities and its supporting facilities, carry out maintenance and maintenance of waste water disposal facilities on a regular basis, seek alternative provision of clean water facilities that can meet the needs of residents, and provide adequate trash can facilities for residents of Rusunawa.